Neuro-Psychiatric Complication of HIV/AIDS in Royal Nepalese Army - Rajbhandari, K C (Medical Journal of Shree Birendra Hospital, 1998)
Neuro-Psychiatric Complication of HIV/AIDS in Royal Nepalese Army